Interim payment application no.033 rev.01 (including supplementary items) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the resubmission of interim payment application no.023 for BRACU new campus project.